Electrochemical Impedance Spectroscopy as a Characterization Method for Enzymatic Fuel Cell Bioanodes - Torrigino, Federica; Nagel, Marcel; Hartmann, Martin; Herkendell, Katharina (ChemElectroChem, 2024)
Enzymatic fuel cells (EFCs) offer renewable energy conversion via highly selective electrode reactions using enzymes as natural catalysts even under mild conditions. Electrochemical impedance spectroscopy (EIS) is a valuable tool for evaluating EFC performance, providing insights into substrate mass transport, enzyme kinetics, and electrode stability. Despite its acknowledged importance, the use of EIS coupled with distribution of relaxation times (DRT) analysis in EFCs research is limited. Our study addresses this gap by employing EIS and DRT analysis to investigate enzyme-based anodic processes, focusing on the bioelectrocatalytic oxidation of glucose catalyzed by glucose oxidase (GOx). Through careful variation of multiple parameters, it was possible to identify three distinct regions in the DRT plot. Each region has been subsequently associated with a key anodic process. The first region (R1) is associated with high-frequency phenomena occurring at the electrodes, primarily due to ionic conduction in the electrolyte. Intermediate-frequency processes are associated to charge transfer kinetics in region 2 (R2). Region 3 (R3) is linked to diffusion processes occurring at low frequencies. This thorough examination offers an insight into the functioning of enzymatic bioelectrodes, which in turn drives improvements in the design and components of biofuel cells to increase their power output.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Distribution of relaxation times; Electrochemical impedance spectroscopy; Enzymes; Fuel cells; Glucose oxidase